Skid Resistance of nano silica modified roller compacted rubbercrete for pavement applications: Experimental methods and response surface methodology - Adamu, M. (Cogent OA, 2018)
Roller compacted concrete (RCC) pavement usage is limited to low-speed roads due to its low skid resistance, caused by the smooth surface texture that makes it unsuitable for use in high-speed traffic pavements. If used in high-speed roadways will lead to increased skid related accidents. In this study, crumb rubber was used as partially replaced with fine aggregate at levels 10, 20, and 30 by volume to produce roller compacted rubbercrete (RCR) so as to improve the skid resistance of RCC pavement, and nano silica was added at 0, 1, 2 and 3 by weight of cementitious materials to mitigate loss of strength with incorporation of crumb rubber. The British Pendulum Number (BPN) was used to measure the skid resistance. Incorporating up to 20 crumb rubber and 2 nano silica increases both skid and impact resistance. The findings showed that RCR with 20 CR and 2 NS can be used for motorways, trunk, and class 1 roads. Finally, response surface methodology was used to develop the relationship between BPN in wet/dry conditions and crumb rubber/nano-silica. The analysis of variance for response surface methodology analysis shows that the quadratic models developed has a very good degree of correlation, and can be used to predict the skid resistance of RCR. The results of multi-objective optimization showed that an optimum mixture can be achieved with a 17.20 volume replacement of fine aggregate and 1.87 nano silica addition by weight of cementitious materials to have the highest skid resistance RCR for pavement applications. Â© 2018 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.